Analisis Senyawa Paracetamol (Acetaminophen) dalam Sampel Urin Menggunakan Metode Kromatografi dan Spektrometri - Dianti Pratiwi; Dila Qhoirul Nisa; Elsya Martia; Ivan Iduljana; Nurma Dwi Rahmawati; Sridevi Anggraini (Syntax Corporation Indonesia, 2022)
Paracetamol (acetaminophen) is a drug that has an analgesic-antipyretic effect. Research has been carried out with the aim of analyzing the compound paracetamol (acetaminophen) in urine qualitatively using Gas Chrotography-Mass Spectrometry (CG-MS) and LC-MS (Liquid Chromathography – Mass Spectrometry). Urine samples were obtained from patients taking paracetamol without changing consumption patterns. The results of the research analysis showed that positive results of acetaminophen-TMS were obtained in urine samples from 1 hour to a day after taking paracetamol tablets but negative results were obtained after more than 1 day of taking tablets.